Cryoablation Versus Radiofrequency Ablation for Hepatic Malignancies: A Systematic Review and Literature-Based Analysis. Issue 49 (December 2015) - Wu, Shunquan; Hou, Jun; Ding, Yingying; Wu, Fuquan; Hu, Yan; Jiang, Qiyu; Mao, Panyong; Yang, Yongping
Abstract : Abstract: The aim of this study is to summarize and quantify the current evidence on the therapeutic efficacy of cryoablation compared with radiofrequency ablation (RFA) in patients with hepatic malignancies in a meta-analysis. Data were collected by searching PubMed, Scopus, and Cochrane databases for reports published up to May 26, 2015. Studies that reported data on comparisons of therapeutic efficacy of cryoablation and RFA were included. The random effects model was used to estimate the pooled relative risks of events comparing cryoablation to RFA for therapy of hepatic malignancies. Seven articles met the inclusion criteria and were included in the meta-analysis. The meta-analysis showed that there was no statistically significant difference in mortality of at least 6 months (odds ratio [OR] = 1.00, 95% confidence interval [CI]: 0.68–1.49) and local tumor progression according to both patients (OR = 1.64, 95% CI: 0.57–4.74) and tumors (OR = 1.81, 95% CI: 0.74–4.38) between cryoablation group and RFA group. However, the risk of complications was significantly higher in the cryoablation group than that in the RFA group (OR = 2.93, 95% CI: 1.15–7.46). When considering the specific complications, only thrombocytopenia (OR = 51.13, 95% CI: 2.92–894.21) and renal impairment (OR = 4.19, 95% CI: 1.34–13.11) but not other complications were significantly higher in the cryoablation group. In conclusion, the 2 methods had almost equal mortality and nonsignificant difference in local tumor progression, with higher risk of complications in cryoablation. Further large-scale, well-designed randomized controlled trials are needed to identify the current findings and investigate the long-term effects of cryoablation compared with RFA for therapy of hepatic malignancies.